Global lactylation is downregulated despite lactate accumulation: lactylome data and functional insights during ISKNV infection - Zhourui Sun; Yinjie Niu; Xiaozhe Fu; Qiang Lin; Xianglin Cao; Hongru Liang; Xia Luo; Baofu Ma; Wenwen Xiao; Ningqiu Li; Jianjun Chen (Fish & Shellfish Immunology, 2026)

Mechanism of neuroinflammation and cardiovascular toxicity induced by tributyltin: Evidence from zebrafish (Danio rerio) models and network toxicology studies - Xianglin Cao; Benfa Lou; Zhourui Sun; Yinyin Wei; Mengyao Qu; Yifan Xu; Qiuxia Kang; Shuaishuai Xie; Qiang Wang; Jianjun Chen (Environmental Pollution, 2026)

Regulation of Reproduction in Delayed Gametophyte of Saccharina japonica (Laminariales, Phaeophyceae): Effects of Light Intensity, Quality and Photoperiod - Xiao Wang; Zhourui Liang; Fuli Liu; Pengyan Zhang; Yanmin Yuan; Yi Liu; Wenjun Wang; Xiutao Sun (Journal of Ocean University of China, 2023)

Insights into the spatio-temporal composition, diversity and function of bacterial communities in seawater from a typical laver farm - Zhourui Liang; Rujie Jia; Tengqin Sun; Wenjun Wang; Chao Wang; Xiaoping Lu (Frontiers in Marine Science, 2022)
Laver is the most widely farmed seaweed with the largest culture area in China. The spatio-temporal variations in composition, diversity, and functional properties of bacteria in seawater as well as the environmental variables of seawater in a large-scale laver farm in China were studied. Both the community richness indices and Shannon index in the laver farming area remained at a relatively stable level during laver cultivation. Fifty-nine prokaryotic phyla were detected in all samples, however, only six of these phyla accounted for 98.84% of all sequences. Proteobacteria, Gammaproteobacteria, Rhodobacterales, Rhodobacteraceae, and Octadecabacter were the most predominant bacterial taxa at different levels of classification. The keystone bacterial taxa were Bacteroidetes, Pseudomonadales, Rhodobacterales, Flavobacteriales, Loktanella , and Pseudoruegeria based on network analysis. Members of representative bacterial biomarker taxa in November may be associated with degradation of algal cell wall polysaccharides. A significant increase in metabolic exchange and transformation nutrients occurred in the seawater during the early and late stage of laver cultivation, indicating that the laver reproductive activities (i.e. the formation/release activities of archeospores and zygotospores) probably drove the variation of metabolic functional diversity of bacterial communities. Based on Mantel test and redundancy analysis, we found the hydrographic parameters (e.g. salinity, temperature, DO, pH) as well as the key carbon (e.g. POC, DOC) and nitrogen parameters (e.g. nitrate, DIN, DON, TDN) were crucial environmental variables to shape the bacterial community composition in the surrounding seawater of laver farm. In a word, our results suggested that the microbial community structure and function significantly changed across the different succession stages during laver cultivation. This work provides new insights on the characteristics of bacterial communities in a large-scale laver farming system and solidifies the importance of laver farming in shaping seawater microbiomes.

Physiological and biochemical responses to light and temperature stress in free-living conchocelis of Neopyropia katadae (Bangiales, Rhodophyta) - Zhourui Liang; Fuli Liu; Wenjun Wang; Pengyan Zhang; Yanmin Yuan; Yi Liu; Haiqin Yao; Rujie Jia; Xiutao Sun; Feijiu Wang (Journal of Applied Phycology, 2022)

Dynamic profile of proteome revealed multiple levels of regulation under heat stress in Saccharina japonica - Fuli Liu; Pengyan Zhang; Zhourui Liang; Wenjun Wang; Xiutao Sun; Feijiu Wang (Journal of Applied Phycology, 2019)

De novo transcriptomics analysis revealed a global reprogramming towards dehydration and hyposalinity in Bangia fuscopurpurea gametophytes (Rhodophyta) - Wenjun Wang; Zonggen Shen; Xiutao Sun; Fuli Liu; Zhourui Liang; Feijiu Wang; Jianyi Zhu (Journal of Applied Phycology, 2019)

Breeding, economic traits evaluation, and commercial cultivation of a new Saccharina variety “Huangguan No. 1” - Fuli Liu; Xiutao Sun; Feijiu Wang; Wenjun Wang; Zhourui Liang; Zhelong Lin; Zhian Dong (Aquaculture International, 2014)

RNA-Seq revealed complex response to heat stress on transcriptomic level in Saccharina japonica (Laminariales, Phaeophyta) - Fuli Liu; Wenjun Wang; Xiutao Sun; Zhourui Liang; Feijiu Wang (Journal of Applied Phycology, 2014)

De novo transcriptome analysis-gained insights into physiological and metabolic characteristics of Sargassum thunbergii (Fucales, Phaeophyceae) - Fuli Liu; Xiutao Sun; Wenjun Wang; Zhourui Liang; Feijiu Wang (Journal of Applied Phycology, 2014)